Online Nurse: Incorporating Islamic Spiritual Mindfulness to Decrease Anxiety during Online Learning among Nursing Students - Agus Santoso; Meidiana Dwidiyanti; Diyan Yuli Wijayanti; Sarah Ulliya; Badrul Munif; Evi Karota; Dudut Tanjung (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Online learning during the COVID-19 pandemic has significantly impacted the physical and psychological health of most college students in Indonesia, especially nursing students. The major psychological impacts that students experience may include increased stress levels and anxiety. Islamic spiritual mindfulness through Online Nurse application is an exercise for emotional regulation with spiritual approach that is carried out online for students to control the situation and choose to accept so that they can reduce their anxiety or stress related to online learning during the COVID-19 pandemic. Objective: This study aimed to determine the effect of Islamic spiritual mindfulness through Online Nurse on reducing anxiety in students undertaking online learning. Methods: This study used a pre-post test quasi-experimental design with a control group. The samples were students undertaking online learning, consisting of 40 students from Qomarul Huda Badaruddin University (UNIQHBA) as the intervention group and 40 students from North Sumatra University (USU) as the control group. Results: There was an effect of Online Nurse on decreasing anxiety levels among students with a p-value of 0.000. Conclusion: Online Nurse can be applied to decrease anxiety among students in certain triggering situations, such as COVID-19 and online learning. Islamic spiritual mindfulness is needed in reducing anxiety. Abstrak: Latar Belakang: Pembelajaran daring di masa pandemi COVID-19 berdampak signifikan terhadap kesehatan fisik dan psikis sebagian besar mahasiswa di Indonesia, khususnya pada mahasiswa keperawatan. Dampak psikologis utama yang dialami mahasiswa adalah meningkatnya tingkat stres dan kecemasan. Mindfulness Spiritual Islam (MSI) melalui Online Nurse merupakan latihan pengaturan emosi melalui aspek spiritual yang dilakukan melalui program online bagi mahasiswa untuk dapat mengendalikan keadaan dan memilih untuk menerima, sehingga dapat mengurangi kecemasan atau stres yang dialami selama menjalani pembelajaran daring di masa pandemi COVID-19. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh MSI melalui Online Nurse terhadap penurunan kecemasan pada mahasiswa yang sedang melakukan pembelajaran online. Metode: Metode penelitian ini adalah penelitian eksperimen semu dengan pre-test post-test control group. Sampel penelitian adalah siswa yang mengikuti pembelajaran online, meliputi kelompok intervensi yang terdiri yang dari 40 siswa dari Universitas Qomarul Huda Badaruddin (UNIQHBA), dan kelompok kontrol yang terdiri dari 40 siswa dari Universitas Sumatera Utara (USU). Hasil: Ada pengaruh MSI melalui Online Nurse terhadap tingkat kecemasan dengan nilai p=0,000. Kesimpulan: Online nurse bisa dipakai untuk menurunkan kecemasan mahasiswa pada saat mengalami situasi tertentu yang memicu kecemasan, misalnya COVID-19 dan kuliah daring. Untuk menurunkan tingkat kecemasan mahasiswa, intervensi MSI mungkin diperlukan.